Community study of toxoplasma antibodies in urban and rural schoolchildren aged 4 to 18 years. Issue 5 (1st November 1997) - Taylor, Mervyn R H; Lennon, Bernadette; Holland, Celia V; Cafferkey, Mary
Abstract : To estimate the prevalence of toxoplasma antibodies in schoolchildren and their association with clinical and environmental data, antibody titres were measured in 1276 children aged 4 to 18 years attending primary and secondary schools. Environmental and clinical data were obtained by questionnaire. Altogether 12.8% (163/1276) of children had antibodies to Toxoplasma gondii with no difference between the sexes. Seroprevalence was higher in country children (16.6% (50/302)) than town children (10.2% (75/737)). The proportion testing positive increased with age in both town and country children. No association with cat ownership was found. Toxoplasma seropositivity was associated with a positive toxocara titre, having had a bitch whelp in the past two years, and having an unwormed dog at home. Lack of energy or tiredness in the last 12 months were the only clinical features associated with a positive titre.